The vampire diaries. The complete seventh season - Dobrev, Nina, 1989-; Wesley, Paul, 1982-; Somerhalder, Ian, 1978-; McQueen, Steven R., 1988-; Graham, Katerina, 1989-; Accola, Candice, 1987-; Smith, L. J. (Lisa J.); Warner Bros. Entertainment; Warner Home Video (Firm); Warner Bros. Television ([Place of publication not identified] : [Publisher not identified], 2015)
After Elena Gilbert succumbs to the sleeping curse at the end of Season Six, those who remain must try to pick up the pieces and move on. Damon attempts to live life as "just Damon". Stefan confronts his first love while growing closer to Caroline, who grieves the loss of both her friend and her mom. Bonnie explores her new powers. Damon and Stefan's mother, Lily, tries to drive a wedge between her sons. Damon is determined to take down his mother and her bank of Heretics - who are hellbent on retaliation and mayhem - while Enzo struggles with his loyalties. With idyllic Mystic Falls apparently falling apart, the action and suspense is grittier and more white-knuckled than ever. Get ready for epic thrills and eternal heartache in all 22 sizzling, supernatural episodes of Season Seven.
Disc 1. Disc 2. Disc 3. Disc 4. Disc 5.
Title from container.
Based upon the book by L.J. Smith.
DVD release of episodes originally broadcast on television in 2013-2014.
Special features: 4 all-new featurettes ; gag reel ; unaired scenes.
Nina Dobrev, Paul Wesley, Ian Somerhalder, Michael Trevino, Steven R. McQueen, Kat Graham, Candice Accola, Zach Roerig.
MPAA rating: Not rated.
Keywords: College students -- Drama; Vampires -- Drama; Brothers and sisters -- Drama; Man-woman relationships -- Drama; Television series; Vampire television programs; Fantasy television programs; Fiction television programs; Video recordings for the hearing impaired